ALCOHOL IN PREVENTION OF CARDIOVASCULAR PATHOLOGY: KNOWN AND UNKNOWN - N. G. Poteshkina; N. S. Krylova; S. K. Adjigaitkanova; A. A. Troshina (Российский кардиологический журнал, 2015)
The review focuses on the data of alcohol influence on cardiovascular health. The recommended and safe prevention dosages are discussed. The data summarized on the risk estimation, of development and progression of ischemic heart damage, heart rhythm disorders, stroke and other vascular complications in long-term alcohol consumption in various dosages. The article should be of interest for physicians, general practitioners, cardiologists, neurologists